Development of high-yielding white maize hybrids with better chapatti-making quality compared to traditionally used local landraces - Arora, Arushi; Das, Abhijit Kumar; Kumar, Ramesh; Sharma, Savita; Kaur, Navjot; Dixit, Shubhank; Kaur, Yashmeet; Saxena, D. C.; Rakshit, Sujay (Frontiers in Nutrition, 2024)
The present research focuses on the nutritional properties and acceptability of high-yielding white maize hybrids compared to accepted low-yielding local yellow and white landraces in India. In this study 156 white maize hybrids were evaluated at three locations. The top nine superior hybrids were selected for testing the physical properties of the maize kernels, proximate composition of flours and chapattis, physical parameters of chapatti, textural properties, sensory evaluation of chapattis and pasting properties of maize flour. The results revealed the superiority of white maize hybrids (WMH), viz., WHM 1, WHM 2 and WHM 8 over the local yellow and white landraces for most of the parameters studied. In sensory analysis, though, the yellow landrace was considered superior by the panelists in terms of colour but the white maize hybrids outperformed in overall sensory analysis and were more acceptable than the yellow and white maize landraces. Thus, the findings of this study will contribute to the genetic enhancement of white maize germplasm and the release of superior white maize hybrids for commercial cultivation. These hybrids will cater for the needs of rural and tribal populations in India who prefer white maize as a staple food, thereby improving their nutritional status.